Deformation of socio-ecological and economic space and interterritorial cooperation in modern conditions - R. F. Gataullin; E. R. Chuvashaeva (Вестник университета)
The article considers the category of socio-ecological and economic space and its main deformations as factors, determining the directions and necessary volumes of interterritorial cooperation. The deformations serve as the result of lack of financing in the development of its elements, their multidirectionality and inefficient use of the existing potential. Besides, we identify the discrepancy between administrative boundaries and service areas as one of the reasons for deformation of the socio-ecological and economic space. Fuller use of available social infrastructure capacities requires joint maintenance of the existing organisations. In the research, the types and depth of the socio-ecological and economic space deformation and factors, causing them, are shown. The level of deformation can be different, which is reflected in the known indicators of deviation from the current threshold values that characterise the preservation of its quality: within the maximum allowable concentration (in ecology), within the framework of existing standards (in saturation of social infrastructure objects), etc. The development of territorial cooperation is considered as an effective factor in overcoming the deformations of the socio-ecological and economic space, allowing to use available potentials better. Moreover, this activity can be aimed at creating a fundamentally new space architecture or improving its elements.